South Estonian Literature: A New Phenomenon with a Centuries-long History - Mart Velsker (Interlitteraria, 2015)
The focus of the article is on South Estonian literature, with an aim to provide a survey of the phenomenon while discussing problems that arise in describing it. These problems are related to the small size of the literary corpus, transformation of modes of description through history, and variations in concepts. Irrespective of the problems, it seems useful to treat South Estonian literature as a separate set of texts; taking the use of South Estonian language as the defining characteristic appears to be the most productive approach. The administrative and linguistic history of South Estonia is different from that of North Estonia and has influenced the development of regional identities. Starting from the 17th century, texts in South Estonian would be published mostly in the form of religious literature, and a South Estonian literary language based on the Tartu dialect was formed. The tradition based on religious literature disappeared at the beginning of the 20th century, while other, and more explicitly literary, opportunities to employ South Estonian language arose. A new wave of South Estonian poetry introduced the second period of South Estonian literature in 1917, during which it was mostly considered as a dialectal branch of Estonian literature. 1987 marked the beginning of a third period that has been characterised by the emergence of literature written in the Võru dialect and the spread of the Võru cultural movement. This most recent stage has brought about changes in the interpretative framework within which South Estonian literature is being discussed.